Solución informática para la gestión de cupos en prácticas pre-profesionales y pasantías. - Mendoza Japón, Jhony Xavier (2021)
The pre-professional practices for a student of higher education tends to be the first mechanism of insertion in a work environment as real as possible, therefore, they are of vital importance for the student, likewise the teacher in charge of this process is committed to verify that the student can perform them. Due to this, the objective of this degree work consists in the construction of a computer solution to manage, disseminate and apply for a pre-professional internship offered during the academic cycle, with this purpose the research question is: Will a computer solution in the Systems Engineering Career of the National University of Loja, optimize the processes of management, dissemination and search for a pre-professional internship or internship? This TT was executed in a purely academic environment and consisted of three phases, in the first phase all the necessary information was collected in order to clarify the process of dissemination and application of a pre-professional internship, resulting in the requirements specification document. As a second phase, the architecture of the application was developed with the Kruchten model, to carry out the respective coding which was done in three environments, the web service was developed in the Laravel/Lumen framework that uses the PHP programming language and that together with MYSQL for database management helped to make the response times in the requests to be fast. On the other hand, the web application was developed with the Angular framework and the mobile application with the Flutter framework, which uses the Dart programming language, both applications are in constant communication with the web service. Subsequently, as a third phase, the acceptance tests were carried out with the teachers responsible for practices and students, which were successful. It is worth mentioning that with the help of the XP software development methodology, each phase was carried out in a more organized manner. In this way it was possible to answer the research question, corroborating that the software solution developed helped in the processes of management and dissemination of a pre-professional practice, as well as in the search and application in the career of Systems Engineering at the National University of Loja. Finally, future works are indicated according to the project developed to improve the functionality of the system. Keywords: pre-professional internship, internship, management, software, dissemination, application, application